2022
DOI: 10.1021/acsomega.1c06010
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Polymer Coating on Silver Nanoparticles for Efficient Plasmonic Enhancement of Fluorescence

Abstract: Surface coating of plasmonic nanoparticles is of huge importance to suppress fluorescence quenching in plasmon-enhanced fluorescence sensing. Herein, a one-pot method for synthesizing polymer-coated silver nanoparticles was developed using a functional polymer conjugated with disulfide-containing anchoring groups. The disulfides played a crucial role in covalently bonding polymers to the surface of the silver nanoparticles. The covalent bond enabled the polymer layer to form a long-term stable coating on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…We believe that this could have also added to the lifetime of the stable enhancement in our experiments. One of the possible ways to protect plasmonic enhancement of silver-coated tips is the use of dielectric protective layers for silver tips as demonstrated in previous studies ( 22 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this could have also added to the lifetime of the stable enhancement in our experiments. One of the possible ways to protect plasmonic enhancement of silver-coated tips is the use of dielectric protective layers for silver tips as demonstrated in previous studies ( 22 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of signal quenching is strong when a metallic tip is in physical contact to samples. Although there have been several successful reports on tip-enhanced photoluminescence/fluorescence measurements using the contact-mode AFM 34 36 , some researchers have also reported that it is better to have a few nanometers of the tip-sample separation for strong signal enhancement in photoluminescence or fluorescence 37 40 . Therefore, we expect that the small-amplitude tapping-mode AFM that we proposed would be an effective way not only for Raman measurements but also for photoluminescence or fluorescence measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, fluorescence enhancements up to three orders of magnitude have been realized in solid assays created by the atomic-layer deposition, by which a thickness-tailorable spacer can be formed at the atomic level to achieve an optimal metalreporter distance for both modes (≈4 nm, slightly varying in spacers of different refractive indices [24,25] ). Approaches using colloidal NPs have proved much more challenging due to the fabrication challenges of wet chemistry (i.e., coating thickness, [24] random adsorption site of the reporter, [26] etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, fluorescence enhancements up to three orders of magnitude have been realized in solid assays created by the atomic-layer deposition, by which a thickness-tailorable spacer can be formed at the atomic level to achieve an optimal metalreporter distance for both modes (≈4 nm, slightly varying in spacers of different refractive indices [24,25] ). Approaches using colloidal NPs have proved much more challenging due to the fabrication challenges of wet chemistry (i.e., coating thickness, [24] random adsorption site of the reporter, [26] etc.). [25] Typical methods for forming the spacer on colloidal NPs include polymer, [24] DNA, [13] SiO 2 , [27][28][29] CTAB, [30,31] and pluronic, [3] among others, most of which only result in single to double-digit fluorescence enhancement factors (EFs) and severe loss of SERS intensity due to the weakened EM field.…”
Section: Introductionmentioning
confidence: 99%